CARBONATION PERFORMANCE OF KAOLIN TREATED WITH GROUND GRANULATED BLAST FURNACE SLAG (Malaysian Journal of Civil Engineering, 2023)
This study is prompted by the fact that currently available information, regarding carbon dioxide (CO2) and ground improvement, is rather limited, as the emphasis in this area, is mainly directed at health and environmental issues. This includes efforts to counter climate change, by reducing the level of carbon dioxide levels in the atmosphere. Nonetheless, several geotechnical researchers have delved into CO2 sequestration, through magnesium-rich materials. Among such materials is ground granulated blast furnace slag (GGBS). This waste material, which contains between 5% to 9% magnesium, and roughly 35% calcium, appears to be a favourable option for CO2 sequestration. The purpose of this study, is to determine the appropriate optimal amount of GGBS (based on the strength value recommended by the Public Works Department), and its effect in terms of durability, for the treatment of kaolin clay, under ambient and carbonated conditions, with a 24-hour carbonation period, subjected to a CO2 pressure of 200 kPa. Compaction, unconfined compressive strength (UCS), and durability (wetting and drying) tests were performed, with various GGBS contents (5%, 15% and 25%), and curing periods (7, 14, 28 and 60 days). The test results indicate an increase in strength of almost 20 times, for kaolin clay treated with 25% GGBS, with a curing period of 60 days (ambient condition). An additional 22.86% increase in strength was registered, for carbonated conditions. The wetting and drying test, also demonstrated that GGBS-treated kaolin was improved in terms of durability, while retaining its strength under wet and dry conditions. Thus, it can be concluded that with an appropriate amount and curing period, GGBS has the potential to stabilize kaolin clay, and contribute towards the realisation of a more sustainable environment, by curbing the amount of CO2 released into the atmosphere.